Long-Term Fate of Lung Autografts Charged with Providing Total Pulmonary Function: II. Hemodynamic, Functional and Angiographic Studies - Veith, Frank J. (1979)
Four dogs underwent autotransplantation of the left lung with immediate ligation of the right pulmonary artery and survived up to five years. Mean pulmonary artery pressures increased from 15 ± 2 mmHg preoperatively to 23 ± 4 mmHg immediately after operation and remained at the level (24 ± 3 mmHg) up to five years operation. Arterial and venous blood gas values, determined while the animals were breathing ambient air spontaneously under light anesthesia, did not deteriorate with time and were within the normal range. The vascular resistance of the transplanted lungs up to five years after operation were not significantly different from those determined immediately after operation and remained lower than preoperative values, indicating that transplanted lungs retain indefinitely the ability to vasodilate with increased blood flow. Periodic angiography performed from 3-5 years after operation confirmed that the right lungs received no pulmonary blood flow and revealed normal vascular morphology except for moderate dilatation of the large arteries in the transplanted left lung. Thus, single transplanted lungs can provide total respiratory function while carrying the entire pulmonary blood flow at tolerable arterial pressures for at least five years without evidence of functional deterioration.